Heterosis for Yield and Yield Components in Rice - Joshi, Bal Kumar (Nepal Agriculture Research Journal, 2011)
It is important to know the degree and direction of hybrid vigor for its commercial exploitation. Heterobeltiosis and standard heterosis were studied in 14 crosses between rice (Oryza sativa L.) cultivars (improved and landraces) and three wild aborted male sterile parents. These crosses showed marked variations in the expression of heterobeltiosis and standard heterosis for yield and yield components. Grain yield manifested highly significant heterobeltiosis and standard heterosis in five crosses. Heterobeltiosis ranging from –55 to 139% and standard heterosis from –11 to 369% were observed. Highest heterotic effect among the yield components was for panicle number plant-1 followed by spikelet number and panicle length. With appropriate choice of parental lines, it is possible to develop F1 rice hybrid possessing distinct yield superiority over the best-inbred lines. Key words: F1; Heterobeltiosis; Hybrid vigor; Oryza sativa; Standard heterosis DOI: http://dx.doi.org/10.3126/narj.v4i0.4857 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 6-12 Uploaded date: 8 June, 2011